In-vitro metabolomics to evaluate toxicity of particulate matter under environmentally realistic conditions. (October 2018) - Sánchez-Soberón, Francisco; Cuykx, Matthias; Serra, Noemí; Linares, Victoria; Bellés, Montserrat; Covaci, Adrian; Schuhmacher, Marta
Abstract: In this pilot study three fractions of particulate matter (PM0.25, PM2.5-0.25, and PM10-2.5 ) were collected in three environments (classroom, home, and outdoors) in a village located nearby an industrial complex. Time-activity pattern of 20 students attending the classroom was obtained, and the dose of particles reaching the children's lungs under actual environmental conditions (i.e. real dose) was calculated via dosimetry model. The highest PM concentrations were reached in the classroom. Simulations showed that heavy intensity outdoor activities played a major role in PM deposition, especially in the upper part of the respiratory tract. The mass of PM10-2.5 reaching the alveoli was minor, while PM2.5-0.25 and PM0.25 apportion for most of the PM mass retained in the lungs. Consequently, PM2.5-0.25 and PM0.25 were the only fractions used in two subsequent toxicity assays onto alveolar cells (A549). First, a cytotoxicity dose-response assay was performed, and doses corresponding to 5% mortality (LC5 ) were estimated. Afterwards, two LC-MS metabolomic assays were conducted: one applying LC5, and another applying real dose. A lower estimated LC5 value was obtained for PM0.25 than PM2.5-0.25 (8.08 and 73.7 ng/mL respectively). The number of altered features after LC5 exposure was similar for both fractions (39 and 38 for PM0.25 and PM2.5-0.25 respectively), while after real dose exposure these numbers differed (10 and 5 for PM0.25 and PM2.5-0.25 respectively). The most metabolic changes were related to membrane and lung surfactant lipids. This study highlights the capacity of PM to alter metabolic profile of lung cells at conventional environmental levels. Graphical abstract: Image 1 Highlights: PM10-2.5, PM2.5-0.25, and PM0.25 were sampled in indoor and outdoor environments. Toxicity and metabolism of A549 cells exposed to PM2.5-0.25 and PM0.25 were studied. PM0.25 showed an overall higher toxicity than PM2.5-0.25 . PM0.25 elicited a higher alteration in metabolism than PM2.5-0.25 . Most of the altered features were lipids present in cell and mitochondrial membranes.